ANALISIS STRATEGI BAURAN PEMASARAN SYARIAH PADA USAHA BIEKUPI BATANG ASAI DI KOTA JAMBI - Anna Silvia; Dedek Kusnadi (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2025)
This study aims to analyze the 9P sharia marketing mix strategy that has not been fully implemented by the Biekupi Batang Asai business in Batang Asai District. The 9P strategy includes: product, price, place, promotion, people, process, physical evidence, partnership, and promise. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. Data validity is obtained through triangulation of techniques and sources, while data analysis is carried out through data reduction, data presentation, and drawing conclusions. First, the results of the study indicate that Biekupi has not fully implemented the 9P marketing mix well enough. The products offered are of high quality, affordable prices according to size and type, the business location is not yet strategic, and promotions are carried out through social media such as WhatsApp, Instagram, and Facebook. The process is carried out according to SOP, with fixed operating hours. The store is neatly arranged and clean as physical evidence, and it has established partnerships with local shops and minimarkets. In addition, Biekupi also keeps its promises to customers by guaranteeing product quality and contributing socially through donations and alms. Second, the obstacles faced by the Biekupi Batang Asai business are that the equipment is still traditional, promotion is still limited, the distance to Jambi is congested, and the coffee bean harvest failed.